ANALISIS MORFO-SEMANTIS ISTILAH-ISTILAH PERMAINAN NEKERAN DI KECAMATAN SEWON KABUPATEN BANTUL - , GALIH ADHI KARTIKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Many types of traditional children's games are rarely played and the longer it seems to be increasingly unpopular, and it is predicted to become extinct. Traditional children's games can be a valuable asset in the formation of cultural identity of a community, society or nation. One of the traditional children's games are nekeran. Nekeran is a traditional game using marbles as a means to play the game. Nekeran game comes from the Dutch word knikker. Nekeran/marbles also called gundu, keneker, kelici, guli, stin (Central Java). This game can be found in various places, especially around communities of Yogyakarta Province (DIY). The game is played by children and adults. In this game, the player have a lot of terms and condition that must be understood. For example gacuk, sladhang, uncal, biri, and etc. These terms are studied and analyzed in morpho-semantic, so that the terms then identified for its intention and its purposes used in the game. This nekeran game besides studied also documented so that traditional children's games will be popular and played again by the children and not vanish in the modern era.